Pengaruh Zakat terhadap Variabel Makroekonomi: Pendekatan VECM - Achmad Mu'afi Ja'far; Eko Suprayitno; Umi Julaihah; Nabila Adenina Zidni Maulida (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2025)
Indonesia's economic growth has not fully translated into an increase in inclusive welfare, because the growth of the economy in the first quarter of 2024 was offset by millions of people who are still below the poverty line and experience limited access to education, health, and decent living standards. This study aims to analyze the causal and cointegration relationships between zakat, economic growth, Human Development Index (HDI), and poverty in Indonesia. Using annual data from 2013 to 2023, this study applies the Vector Error Correction Model (VECM) approach, including stationarity tests, optimal lag determination, Johansen cointegration test, Granger causality. The results indicate the existence of long-term relationships among the variables, with zakat exerting a significant influence on reducing poverty and improving HDI. However, the influence of zakat on economic growth is relatively insignificant. This research contributes to the Islamic economics literature and provides a strategic policy foundation for optimizing national zakat management.